FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PRODUK ASURANSI SYARI'AH - Kuat Ismanto (Jurnal Hukum Islam, 2016)
This research wants to prove the influence of religiosity on purchasing decisions of sharia insurance, with the marketing mix as a moderator variable. There are four aspects of marketing mix that have been observed such as location, price, promotion, and product. Data were obtained by distributing questionnaires to participants of sharia insurance. Data were analyzed by SPSS. The result showed that the factor of religiosity, by placing the marketing mix as a moderator variable, reinforce on purchasing decision rather than no marketing mix.